Transforming combustion research through cyberinfrastructure (National Academies Press, 2011)
Combustion has provided society with most of its energy needs for millennia, from igniting the fires of cave dwellers to propelling the rockets that traveled to the Moon. Even in the face of climate change and the increasing availability of alternative energy sources, fossil fuels will continue to be used for many decades. However, they will likely become more expensive, and pressure to minimize undesired combustion by-products (pollutants) will likely increase. The trends in the continued use of fossil fuels and likely use of alternative combustion fuels call for more rapid development of improved combustion systems. In January 2009, the Multi-Agency Coordinating Committee on Combustion Research (MACCCR) requested that the National Research Council (NRC) conduct a study of the structure and use of a cyberinfrastructure (CI) for combustion research.